Impact of the National Education Policy 2020 on Modern College Teachers and Contemporary Teaching Methods: राष्ट्रीय शिक्षा नीति 2020 का आधुनिक महाविद्यालयीन शिक्षकों एवं वर्तमान शिक्षण पद्धतियों पर प्रभाव - Sanju (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
The National Education Policy (NEP) 2020 is a visionary initiative aimed at bringing qualitative transformation to the Indian higher education system. This policy seeks to strengthen the quality of education, inclusion, flexibility, and global relevance. College teachers play a key role in the effective implementation of this policy, as extensive changes have been proposed in their academic responsibilities, teaching approaches, and institutional participation. The objective of the present research paper is to analyze the impact of NEP 2020 on modern college teachers and prevailing teaching methodologies. This study is based on a descriptive and analytical research method and relies on secondary sources such as policy documents, UGC guidelines, and related academic literature. The study clearly indicates that NEP 2020 promotes a shift from a teacher-centered and examination-oriented system to a learner-centered, multidisciplinary, and experiential learning approach. However, challenges related to institutional preparedness, digital resources, and teacher capacity also emerge during its implementation. In conclusion, it can be stated that NEP 2020 presents vast possibilities for positive transformation in higher education, but its success depends on continuous training, institutional collaboration, and a participatory approach. Abstract in Hindi Language: राष्ट्रीय शिक्षा नीति 2020 भारतीय उच्च शिक्षा व्यवस्था में गुणात्मक परिवर्तन लाने की एक दूरदर्शी पहल है। यह नीति शिक्षा की गुणवत्ता, समावेशन, लचीलापन तथा वैश्विक प्रासंगिकता को सुदृढ़ करने का प्रयास करती है। इस नीति के प्रभावी क्रियान्वयन में महाविद्यालयीन शिक्षक प्रमुख भूमिका निभाते हैं, क्योंकि उनकी शैक्षणिक जिम्मेदारियों, शिक्षण दृष्टिकोणों तथा संस्थागत सहभागिता में व्यापक परिवर्तन प्रस्तावित किए गए हैं। प्रस्तुत शोध पत्र का उद्देश्य NEP 2020 के अंतर्गत आधुनिक महाविद्यालयीन शिक्षकों तथा प्रचलित शिक्षण पद्धतियों पर पड़ने वाले प्रभावों का विश्लेषण करना है। यह अध्ययन वर्णनात्मक एवं विश्लेषणात्मक शोध पद्धति पर आधारित है तथा नीति दस्तावेजों, UGC दिशानिर्देशों एवं संबंधित शैक्षणिक साहित्य जैसे द्वितीयक स्रोतों पर आधारित है। अध्ययन से स्पष्ट होता है कि NEP 2020 शिक्षक-केंद्रित एवं परीक्षा-प्रधान प्रणाली से हटकर शिक्षार्थी-केंद्रित, बहुविषयी तथा अनुभव आधारित अधिगम को प्रोत्साहित करती है। हालांकि, इसके क्रियान्वयन में संस्थागत तैयारी, डिजिटल संसाधनों तथा शिक्षक क्षमता से जुड़ी चुनौतियाँ भी सामने आती हैं। निष्कर्षतः यह कहा जा सकता है कि NEP 2020 उच्च शिक्षा में सकारात्मक परिवर्तन की व्यापक संभावनाएँ प्रस्तुत करती है, किंतु इसकी सफलता सतत प्रशिक्षण, संस्थागत सहयोग तथा सहभागी दृष्टिकोण पर निर्भर करती है। Keywords: राष्ट्रीय शिक्षा नीति 2020, उच्च शिक्षा, महाविद्यालयीन शिक्षक, शिक्षण पद्धति, शैक्षणिक परिवर्तन